PARTISIPASI PEREMPUAN DALAM EKONOMI INKLUSIF - Elsy Renie (State Institute of Islamic Studies Batusangkar, 2019)
Gender inequality has become an issue in some countries. Although this inequality appear in various indicators such as economy, there is an improvement in the condition of women. The bias perception gives greater impact on women's work in all fields which are not as high position as men’s work. The concept of inclusive economic development provides equal opportunities for men and women to actively participate in the economic sector. Then, the involvement of women in the inclusive economic sector still needs empowerment and literacy for the percentage of male involvement is more dominant than women. This research is a normative study that raises the theme of women's involvement in an inclusive economy. The aim of this research is to find out the women’s participation in inclusive economy both in Indonesia and in other developing countries. This research concludes that the role of women in an inclusive economy has shown development. It can be seen from two indicators. First, the women’s participation in employment is almost the same with men. Second, the woman’s participation in education, despite they are still left behind by men, their existence in education field is increasing than previous year.